Problems lead to the low level of academic achievement in the evening school: suggestions and solutions (Journal Of Educational and Psychological Researches, 2022)
Academic achievement is a professional standard for measuring student levels in the first stages. Therefore, any indication of the level of achievement makes us in an attempt to employ students in evening schools. The researcher has developed a closed questionnaire of (36) paragraphs. A total of (164) male and (24) female students were chosen from evening schools. The result of this research revealed that the number of students was a reason for the low level of their achievement, the lack of laboratories, educational methods, and techniques of the most prominent problems confirmed by students in these schools. In addition, to support educational institutions with their necessary needs. The most important conclusion in this research is that the more severe the problems, the greater the impact will be in reducing the level of academic achievement among learners. The researcher recommended educational institutions to remove congestion in schools and classes.